Implementing Agile Scrum in Dental Clinic Finance Software Development - Sihombing, Denny Jean Cross (Jurnal Ekonomi, 2024)
This research addresses a crucial problem in the financial management of dental clinics in the digital era, requiring effective solutions to enhance efficiency and quality of dental healthcare services. The Agile Scrum methodology is implemented in the development of financial software for dental clinics as a responsive and adaptive solution to the complexity of financial processes, limited financial resources, and the need for real-time monitoring. Through a combination of qualitative interviews with stakeholders and quantitative data analysis, this study evaluates the effectiveness of Agile Scrum in addressing financial management challenges faced by dental clinics. The research findings indicate that the implementation of Agile Scrum in financial software development has made a significant contribution by improving operational efficiency, accuracy of financial management, and user satisfaction, thereby making an important contribution to enhancing the quality of dental healthcare services.